Repositioning ‘old’ drugs to treat rare diseases: arguing from the mechanism of action - Drent, Marjolein; Bast, Aalt; Bootsma, Hans-peter; Deneer, Vera (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
NA